Biogenic emissions-related ozone enhancement in two major city clusters during a typical typhoon process. (May 2023) - Xu, Jiawei; Zhou, Derong; Gao, Jian; Huang, Xin; Xue, Likun; Huo, Juntao; Fu, Qingyan; Ding, Aijun
Abstract: Typhoons could influence air quality via multiple chemical and physical process and has attracted much scientific attention. A typical typhoon, In-Fa, passed through Yangtze River Delta (YRD) and Jing-Jin-Ji (JJJ) after it made a landfall in China. Under such influences, two city clusters both experienced high ozone (O3 ) concentrations, with JJJ about 5 days earlier than YRD. Data from several environmental monitoring sites and three regional sites indicated that cross-regional transport and biogenic emissions both played an important role in O3 formation. During the typhoon process, O3 precursors were first transported from YRD and its surrounding areas to JJJ due to the summer monsoon. After that, air masses from northern China returned to YRD due to the peripheral winds of the typhoon. High O3 was concentrated in downwind regions, causing fast secondary formation. The peripheral winds and downdrafts of typhoon led to high temperature and stagnant weather, favorable for biogenic emissions. Observed isoprene concentration was doubled. The ratio of isoprene to VOCs also increased by around 5%. The modeling results showed the contribution of BVOCs to O3 could reach 10 ppb in JJJ when the typhoon made its landfall in YRD. When the typhoon moved to JJJ, the cross-transport of air masses from northern China to YRD contributed half of biogenic-emission-related O3 . Our research extends the knowledge into the importance of biogenic emissions to O3 and cross-regional transport during a typhoon process. Highlights: High O3 concentrations occurred in two city clusters, JJJ and YRD, during a typhoon process. Cross-regional transport connected pollutants and precursors in two city clusters. Isoprene was enhanced in peripheral areas as the typhoon moved, contributing to O3 in downwind areas.